Contributions of IL-33 in Non-hematopoietic Lung Cells to Obstructive Lung Disease - Drake, Li Y.; Prakash, Y. S. (Frontiers in Immunology, 2020)
Interleukin (IL)-33 plays important roles in pulmonary immune responses and lung diseases including asthma and chronic obstructive pulmonary disease (COPD). There is substantial interest in identifying and characterizing cellular sources vs. targets of IL-33, and downstream signaling pathways involved in disease pathophysiology. While epithelial and immune cells have largely been the focus, in this review, we summarize current knowledge of expression, induction and function of IL-33 and its receptor ST2 in non-hematopoietic lung cells in the context of health and disease. Under basal conditions, epithelial cells and endothelial cells are thought to be the primary resident cell types that express high levels of IL-33 and serve as ligand sources compared to mesenchymal cells (smooth muscle cells and fibroblasts). Under inflammatory conditions, IL-33 expression is increased in most non-hematopoietic lung cells, including epithelial, endothelial, and mesenchymal cells. In comparison to its ligand, the receptor ST2 shows low expression levels at baseline but similar to IL-33, ST2 expression is upregulated by inflammation in these non-hematopoietic lung cells which may then participate in chronic inflammation both as sources and autocrine/paracrine targets of IL-33. Downstream effects of IL-33 may occur via direct receptor activation or indirect interactions with the immune system, overall contributing to lung inflammation, airway hyperresponsiveness and remodeling (proliferation and fibrosis). Accordingly from a therapeutic perspective, targeting IL-33 and/or its receptor in non-hematopoietic lung cells becomes relevant.